Impact of Oral Health Status on Future Dietary Intake and Dietary Quality in Older Adults in Northern Ireland: A Longitudinal Analysis (P18-080-19) - Logan, Danielle (Curr Dev Nutr, 2019)
OBJECTIVES: Evidence linking oral health status with dietary intake and quality in older adults is inconsistent and limited by few prospective studies conducted to date. This study investigated whether oral health status, defined as number of natural teeth and prosthodontic rehabilitation, had an impact on future dietary intake and dietary quality in older Northern Irish (NI) men. METHODS: This study involved older men [n = 1096, mean = 63.5(2.9) years] from the Prospective Epidemiological Study of Myocardial Infarction (PRIME). A dental examination was undertaken at baseline (2001–2006) and oral health status was defined as: 21–28 teeth without dentures (n = 453), 21–28 teeth with dentures (n = 111), 1–20 teeth without dentures (n = 99), 1–20 teeth with dentures (n = 354), and edentate with dentures (n = 79). A food frequency questionnaire administered in 2015 derived intakes of major food groups and diet quality scores were characterised by the Dietary Diversity Score (DDS) and Mediterranean Diet Score (MDS). Associations between oral health status, food intake and diet quality scores were assessed using regression models adjusted for potential confounders including, age, socio-economic status, smoking and alcohol. RESULTS: In fully adjusted models, the mean dietary intake of fruit, vegetables and nuts significantly differed between oral health status groups. In comparison to edentate men with dentures, the mean fruit intake was significantly higher in each dentate group: 21–28 teeth without dentures (P = 0.001), 21–28 teeth with dentures (P = 0.001), 1–20 teeth without dentures (P = 0.04), and 1–20 teeth with dentures (P = 0.03). The mean DDS was significantly higher amongst men with 21–28 teeth without dentures, compared to those with 1–20 teeth without dentures (P = 0.001), 1–20 teeth with dentures (P < 0.001), and edentate with dentures (P < 0.001), and mean MDS results were similar. Compared to men with 21–28 teeth without dentures, edentate men with dentures were 64% less likely to achieve the dietary guideline of 2 portions/day (P = 0.01). CONCLUSIONS: A greater number of natural teeth was associated with a higher future intake of fruit, vegetables and nuts, as well as higher dietary quality scores, in older NI men. Interventions should optimise retaining natural teeth to help improve dietary intake and quality in older adults. FUNDING SOURCES: Department of Economy funded PhD.